New method to separation and purification of two bioactive compounds from powder of turmeric plant by RP-HPLC technique - Dhuha Jumah Dakhal Ramadan; Huda Zaid Ibraheem Mohamed; Kawthar Mutashar Nasser Khalif; Mariam Manaf Qasim Jaber; Ahmed Abbas Hilal Hazza (Genius Journals, 2024)
Two compounds were separated successfully. The used method was suitable for getting a high purified compound for each one . There is the ability to get more than one high purified compound from alcoholic extract for curcumin
Keywords: turmericplant; RP-HPLC; separation